MANAGEMENT OF ISLAMIC UNIVERSITY IN INDONESIA: A LITERATURE STUDY - Rahmad Rafid; M. Chairul Chafis; A. Qomarudin; Ahmad Munjin Nasih (Four Son Scholarship, 2024)
This study aims to analyze and describe the management of Islamic universities in Indonesia. This research is qualitative with the type of library approach (library research). The management of Islamic universities plays a crucial role in advancing Islamic education and producing a young generation of Muslims who are knowledgeable, moral, and ready to face the challenges of the Times. With good management and adaptive to change, PTAI can continue to grow and provide great benefits for the people and nation. The management of Islamic universities plays a very important role in ensuring the success of Islamic education. By facing challenges and implementing the right strategies, PTAI can continue to develop and make significant contributions to society and the nation the management of Islamic universities is a complex field and demands attention to various aspects of Education, Resource Management, as well as interaction with stakeholders. Improving the quality and relevance of education, effective and efficient management, and student character development are some of the key factors to achieve the goals of the institution. Through the right strategy and the implementation of good governance, Islamic religious universities can become institutions that excel in providing quality education, producing useful research, and contributing positively to society. Thus, Islamic universities will be able to produce graduates who are not only academically competent, but also with integrity and noble character, ready to face global challenges while still holding fast to Islamic values